Concomitant Esodeviation and Diplopia in Adults in Modern Conditions of Increasing Screen Visual Load - Litynska, Valentyna; Petrenko, Oksana (The Ukrainian Scientific Medical Youth Journal, 2026)
the increase in screen-related visual load over the past decade, further intensified during the COVID-19 pandemic, appears to be associated with a rising prevalence of concomitant esotropia and symptomatic diplopia in adults, particularly among young myopic individuals. This trend likely reflects changes in visual behavior and highlights the importance of early diagnosis and identification of underlying mechanisms. To investigate concomitant esotropia and diplopia in adults under contemporary conditions of increased screen-related visual load. An analytical review of published clinical, pathophysiological, and epidemiological studies on concomitant esotropia and diplopia was performed. Diplopia is a sensory symptom defined as the perception of two images of a single object with horizontal, vertical, or oblique separation, resulting from impaired interaction between the sensory and motor components of the visual system. Diplopia associated with concomitant esotropia may develop due to decompensation of fusion mechanisms and a reduction in divergence reserves, leading to instability or loss of binocular vision. Acute acquired comitant esotropia (AACE), divergence insufficiency (DI), and age-related distance esotropia associated with sagging eye syndrome (ARDE/SES) represent clinically similar but pathogenetically heterogeneous conditions. Increased screen time has been associated with myopia progression and may contribute to the development of these conditions, particularly in younger patients. In younger individuals, the predominant mechanism is likely functional decompensation of fusion with selective reduction of divergence reserves. In contrast, morphological changes of the extraocular motor apparatus appear to play a greater role in older patients. These conditions may partially overlap in clinical presentation and disease course, which can complicate differential diagnosis. Strabometric assessment, evaluation of fusion reserves, and morphological analysis of the extraocular motor system (including orbital MRI) are essential for identifying the underlying mechanism. The presence of functional or structural changes influences clinical decision-making and determines the choice of treatment strategy, ranging from conservative approaches to surgical intervention. However, unified diagnostic and therapeutic protocols remain limited, indicating the need for further standardization. Increased screen-related visual load appears to be an important factor associated with a higher prevalence of concomitant esotropia in myopic adults. AACE, DI, and ARDE/SES represent a spectrum of clinically similar but pathogenetically distinct conditions involving functional or structural mechanisms. Identification of the underlying mechanism is important for clinical management and may contribute to the development of standardized diagnostic and therapeutic approaches.